Keaktifan Belajar Siswa Pada Mata Pelajaran IPS Ditinjau Dari Metode Mengajar Guru dan Fasilitas Belajar Pada Siswa Kelas VIII MTsN Plupuh Sragen Tahun Ajaran 2016/2017 - Pradita, Dian; , Dr. Djalal Fuadi, M.M (2016)
The purpose of this study was to determine the effect of students 'perception on the use of methods of teaching and learning facilities to students' learning activeness in social studies students at class VIII MTsN Plupuh Sragen academic year 2016/2017. This research is quantitative research with associative approach that examine the relationship between variables. The study population was all students of class VIII MTsN Plupuh Sragen academic year 2016/2017, amounting to 312 students. Samples taken as many as 78 students. The sampling technique using random sampling. The data collection technique using a questionnaire that had been tested in advance and tested for validity and reliability test. Data analysis technique used is multiple regression analysis, t-test, F, R2 test, as well as the relative contribution and effective. The results showed that: (1) Perceptions of students on teaching methods teachers positive effect on students' learning activeness at the 5% significance level. Contributions of students' perceptions about the teaching methods of teachers to activity of learning is at 25.1%; (2) Facilities learn positive effect on students' learning activeness at the 5% significance level. Contribution to the activity of learning learning facilities was 35.7%; (3) Perceptions of students on teaching methods of teachers and learning facilities jointly positive effect on the activity of class VIII student MTsN Plupuh Sragen academic year 2016 / 2017pada significance level of 5%. Overall variables influence students' perceptions about the teaching methods of teachers and learning facilities contributed by 60.8% and the rest influenced by other factors to the activity of learning students. That is the level determined by the students' learning activeness of students' perceptions of teachers' teaching methods and student learning facility completeness.